COMMUNITY PARTICIPATION IN TOURISM DEVELOPMENT - Grace Amin; Filda Rahmiati; Yunita Ismail; Togar Simatupang; Dwi Larso (President University, 2021)
Riau Islands is one of the provinces in Indonesia that has exotic and potential tourist attractions. Batam and Bintan are one of the tourist magnetism in Riau Islands. This study aims to examine the participation of local people in tourism growth. Researchers collected primer data through interviews with representative of local government, stakeholders in tourism industry and communities. The result show that local government has programs for tourism expansion such as empowerment of local communities, conduct cultural activities, build facilities and infrastructures. Even though local government has created tourism establishment programs but local community participation is also an important factor for sustainability of tourism development.Keywords: Community participation, tourism development, Riau Islands